2010
DOI: 10.5194/acp-10-10145-2010
|View full text |Cite
|
Sign up to set email alerts
|

GOME-2 observations of oxygenated VOCs: what can we learn from the ratio glyoxal to formaldehyde on a global scale?

Abstract: Abstract. Collocated data sets of glyoxal (CHO.CHO) and formaldehyde (HCHO) were retrieved for the first time from measurements of the Global Ozone Monitoring Experiment-2 (GOME-2) during the first two years of operation in 2007 and 2008. Both oxygenated Volatile Organic Compounds, OVOC, are key intermediate species produced during the oxidation of precursor hydrocarbons. Their short lifetime of a few hours in the lower troposphere links them to emission sources and makes them useful tracers of photochemical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
133
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(161 citation statements)
references
References 73 publications
19
133
2
2
Order By: Relevance
“…Outside the Tropics, the mean glyoxal VCDs are lower and depend strongly on the season, reflecting the seasonal patterns in the emissions of glyoxal precursors and especially isoprene. In general, the observed glyoxal fields qualitatively agree with those recently measured by Vrekoussis et al (2010), except over remote oceans where their columns are low-biased due to the glyoxal-liquid water spectral interferences. Overall, the glyoxal vertical columns increase during the local summer months.…”
Section: Observed Gome-2 Glyoxal Vertical Columnssupporting
confidence: 78%
“…Outside the Tropics, the mean glyoxal VCDs are lower and depend strongly on the season, reflecting the seasonal patterns in the emissions of glyoxal precursors and especially isoprene. In general, the observed glyoxal fields qualitatively agree with those recently measured by Vrekoussis et al (2010), except over remote oceans where their columns are low-biased due to the glyoxal-liquid water spectral interferences. Overall, the glyoxal vertical columns increase during the local summer months.…”
Section: Observed Gome-2 Glyoxal Vertical Columnssupporting
confidence: 78%
“…By analyzing satellite measurement results, Vrekoussis et al (2010) concluded that high R GF can represent regions strongly influenced by biogenic emissions. However, based on the in situ observations, DiGangi et al (2012) found that the anthropogenic emissions have positive impact on R GF .…”
Section: Influences On the Chocho To Hcho Ratiomentioning
confidence: 99%
“…As illustrated by Vrekoussis et al (2010) and DiGangi et al (2012), the CHOCHO to HCHO ratio (R GF ) can be used as an indicator of anthropogenic or biogenic impact on photochemistry. When HCHO and CHOCHO are entirely photochemically formed, R GF is determined by the relative strength of production and destruction of HCHO and CHOCHO.…”
Section: Influences On the Chocho To Hcho Ratiomentioning
confidence: 99%
See 2 more Smart Citations